ANALISIS PERLAKUAN AKUNTANSI PENYUSUTAN ASET TETAP PT TAHTA AULIA PERKASA SAMARINDA (PSAK NO. 16) - Harta, Survita Budi (EKONOMIA, 2018)
The aims of this research was to analyze and discuss the accounting practice of fixed asset depreciation in PT Tahta Aulia Perkasa Samarinda based on Statement of Accounting Standard Number 16 Fixed Asset.Theory used in this research were depreciation theory and Statement Of Accounitng Standard Number 16. The analyze measure was used Statement of Accounting Standard wich compare between the corporate fixed assets recording such as practicing while admition, practicing while admittioan measurement, practicing while measurement after admition, practicing when disclose all information about fixed asset regulation, with the Accounting Standard Regulation.The Method used was Statement of Accounting Standard wich compare all those aspects then recalculate the depreciation cost, accumulated depreciation cost, and book value of fixed asset recoreded using the fit standard calculation method.The result of this research was PT Tahta Aulia Perkasa had implemented the record of its fixed asset based on Statement of Accounting Standard. Measurement while admition had the suitable practice based on Accounting Standard. The measurement after admition of their fixed asset was out of fit with their standard, which can make the record of their depreciation value in unstandarizeble condition. Disclosure aspects implemented had the suitable practicing with standard. The practice of fixed asset in PT Tahta Aulia Perkasa had several corrections need to be remark to make their practicing in fixed asset proper with their Statement of Accounting Standard (PSAK) Number 16 Fixed Asset.